2017
DOI: 10.5301/hipint.5000540
|View full text |Cite
|
Sign up to set email alerts
|

Higher UHMWPE Wear-Rate in Cementless Compared with Cemented Cups with the Saturne® Dual-Mobility Acetabular System

Abstract: At short term follow-up, the mean wear-rate in old and low demand patients was high, correlated to activity, and was above the generally accepted osteolysis threshold (0.1 mm/yr.). Cementless HA-coated cups had higher wear-rate than cemented cups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Dual mobility (DM) cups became increasingly popular in recent years, as they proved effective at preventing articular instability, by virtue of increased 'jump distance' and ratio of head-to-neck diameter [25,47]. Though the initial 'Bousquet' cup was prone to intra-prosthetic dislocations (IPD) and aseptic loosening [37,40,42,46], design improvements over the past decades resolved many shortcomings of DM cups, thanks to enhanced press-fit and bioactive coatings [10,31], as well as more durable liners made of ultra-high molecular weight polyethylene (UHMWPE) [37,45].…”
Section: Introductionmentioning
confidence: 99%
“…Dual mobility (DM) cups became increasingly popular in recent years, as they proved effective at preventing articular instability, by virtue of increased 'jump distance' and ratio of head-to-neck diameter [25,47]. Though the initial 'Bousquet' cup was prone to intra-prosthetic dislocations (IPD) and aseptic loosening [37,40,42,46], design improvements over the past decades resolved many shortcomings of DM cups, thanks to enhanced press-fit and bioactive coatings [10,31], as well as more durable liners made of ultra-high molecular weight polyethylene (UHMWPE) [37,45].…”
Section: Introductionmentioning
confidence: 99%
“…Further to doubts related to the efficacy of the DMC concept there are concerns regarding its safety. The concept of a large polyethylene liner ensheathed between two metal surfaces might increase polyethylene wear (Tabori-Jensen et al 2018) and the subsequent risk of aseptic loosening (Caton et al 2014), and an increased risk of periprosthetic joint infections (PJI) is also reported after the use of DMC (Kreipke et al 2019), although this notion has been contested (Jobory et al 2019). A design-specific complication of DMC is intraprosthetic dislocation (Philippot et al 2013, Darrith et al 2018.…”
mentioning
confidence: 99%